Genetic Blockade of NAAA Cell-specifically Regulates Fatty Acid Ethanolamides (FAEs) Metabolism and Inflammatory Responses - Xie, Xiaohua; Li, Yitian; Xu, Sennan; Zhou, Pan; Yang, Longhe; Xu, Yaping; Qiu, Yan; Yang, Yungang; Li, Yuhang (Frontiers in Pharmacology, 2022)
N-Acylethanolamine acid amidase (NAAA) is a lysosomal enzyme responsible for the hydrolysis of fatty acid ethanolamides (FAEs). However, the role of NAAA in FAEs metabolism and regulation of pain and inflammation remains mostly unknown. Here, we generated NAAA-deficient (NAAA-/-) mice using CRISPR-Cas9 technique, and found that deletion of NAAA increased PEA and AEA levels in bone marrow (BM) and macrophages, and elevated AEA levels in lungs. Unexpectedly, genetic blockade of NAAA caused moderately effective anti-inflammatory effects in lipopolysaccharides (LPS)-induced acute lung injury (ALI), and poor analgesic effects in carrageenan-induced hyperalgesia and sciatic nerve injury (SNI)-induced mechanical allodynia. These data contrasted with acute (single dose) or chronic NAAA inhibition by F96, which produced marked anti-inflammation and analgesia in these models. BM chimera experiments indicated that these phenotypes were associated with the absence of NAAA in non-BM cells, whereas deletion of NAAA in BM or BM-derived cells in rodent models resulted in potent analgesic and anti-inflammatory phenotypes. When combined, current study suggested that genetic blockade of NAAA regulated FAEs metabolism and inflammatory responses in a cell-specifical manner.